Technology acceptability for medical assistance - Ziefle, Martina; Wilkowska, Wiktoria (2010 4th International Conference on Pervasive Computing Technologies for Healthcare, 2010)
In this research we examine the age-specific acceptance motives of medical assistive technologies assessing the general openness of using these technologies as well as estimating potential barriers, which may impede a successful rollout. 122 respondents (20 - 80 years) participated in a survey, in which they were asked to evaluate the pros and cons of the usage of medical assistive technologies, acceptance motives and potential utilization barriers. In order to understand the complex nature of acceptance, personal variables (age, technology generation gender) as well as participants' learning history with technology (technical experience, subjective technical confidence and general attitudes towards the usage of technologies) were related to each other. Outcomes show that, overall, there is a quite positive motivation regarding the usage of medical technology, though, the perceived usage barriers are weighted more decisive for the acceptability of medical technology than the positively evaluated using motives. Overall, it was revealed that acceptance issues should be considered in order to proactively design a successful rollout of medical technologies.